Exergy Analysis on Performance of Groundnut Solar Dryer with Forced Convection. Issue 1 (February 2021) - Subramaniyan, C; Prakash, KB; Kalidasan, B; Bhuvanesh, N; Amarkarthik, A
Abstract: The moisture present in the farming yields and in seeds is one of the greatest affecting factors which are playing a major role in storing it for longer days. The quality of products can be increased by preventing the formation of bacteria, yeast, etc. The moisture content present in the groundnut must be between 10 to 15% (weight basis). In this study a numerical analysis was investigated on a solar dryer, which is used to diminish the moisture content present in the groundnut to preserve it for longer days. The performance analyses of forced convection solar dryer with dryer compartment were analysed based on local ambient conditions at sathyamangalam for various required design and operating parameters such as moisture removal rate, air mass flow rate, air inlet, and outlet temperature. The proposed basic solar collector aperture area is about 2 m 2 which is made of the copper plate as an absorber plate coated with black powder coating for better absorption. The moisture content present in the freshly harvested groundnut varies from 25-30 % (weight basis). The analysis was done for drying groundnut to remove the moisture content to the required moisture level of 10% by utilizing solar energy. The results from the study illustrate that the Efficiency of dryer is a maximum of 39.2% for the optimized mass flow rate of 0.022 kg/s and also it was found that the dryer overall efficiency and average collector temperature is gradually decreasing for increasing the mass flow rate.